Serum Leptin Concentration is Correlated to Insulin Resistance in Polycystic Ovary Syndrome (PCOS) Patients - Arsyi Adliah Anwar; Nusratuddin Abdullah; Andi Nursanty Padjalangi; Firdaus Hamid; Nasrudin Andi Mappeware; Efendi Lukas (Molecular and Cellular Biomedical Sciences, 2021)
Background: Leptin resistance which leads to excessive circulating leptin levels is thought to affect ovarian function. This study aimed to study the correlation between serum leptin levels with insulin resistance in patients with polycystic ovary syndrome.Materials and Methods: This cross-sectional study was undertaken in several teaching hospitals in Makassar, Indonesia. We included patients diagnosed with polycystic ovary syndrome (PCOS) aged 18-40 years old. Serum leptin levels were examined in all eligible subjects using the enzyme-linked immunosorbent assay (ELISA) method. The results obtained were further analyzed statistically.Results: Approximately 53 PCOS subjects were included in this study, 25 subjects with insulin resistance and 28 subjects without insulin resistance. After examining serum leptin levels, we found that leptin is directly proportional to insulin resistance (p<0.001). We even found a strong positive correlation between serum leptin levels with homeostatic model assessment for insulin resistance (HOMA-IR) levels (r=0.659; p<0.001). Leptin was found to be independent of HOMA-IR, not influenced by confounding factors such as body mass index (BMI) (p=0.090).Conclusion: There was a significant correlation between serum leptin levels and HOMA-IR values in PCOS patients. This correlation was found to be significant regardless of patient's BMI, therefore is considered to have a direct effect on insulin resistance in PCOS.Keywords: polycystic ovary syndrome, leptin, insulin resistance, HOMA-IR